Clinico-epidemiological Characteristics and Long-term Surgical Outcomes in Patients with Glomus Tumor: A Retrospective Study - Keshavamurthy Vinay; Tarun Narang; N Roshini; Narayanan Baskaran; Ashwini Reddy; Sandeep Patel; Sunil Dogra (Indian Dermatology Online Journal)
Background: Glomus tumors are painful neoplasms arising from the glomus bodies generally over fingertips. Being rare tumors, data on long-term surgical outcomes is scarce. Aim and Objective: This study aimed to describe the clinico-epidemiological characteristics, and surgical outcomes, assess patient satisfaction, rates of recurrence, and surgical complications of glomus tumor. Patients and Methods: This was a retrospective study of patients with glomus tumors of nail apparatus who attended the dermatosurgery clinic and underwent surgery in the last 10 years (2013–2023). The demographic details, presenting symptoms, investigations, surgical procedures, and follow-up were analyzed. Results: There were 25 patients with glomus tumor with a female preponderance, and fingers were affected (23/25) in the majority. The most common symptom was pain present in all patients. Reddish-blue discoloration of the nail bed was seen in 17 (68%) patients and nail plate changes in the form of dystrophic nails and longitudinal splitting at presentation were noted in five (20%) patients. All patients were treated surgically by transungual excision. The commonest immediate complication was pain, present in all patients. Incomplete nail plate formation and longitudinal split post-surgery were noted in six patients (24%). The median duration of follow-up was 5 years post-surgery. All the patients were satisfied after surgery having complete pain relief without any recurrence during the follow-up period. Limitations: Small sample size, retrospective study design, and unavailability of onychoscopy and imaging studies (ultrasonography and/or magnetic resonance imaging) in all cases. Conclusion: Surgical excision of glomus tumors was curative with minimal risk of recurrence. Patients were contended with pain relief and improved quality of life.